2023
DOI: 10.1038/s41525-022-00343-8
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic ATG4D variants are associated with a neurodevelopmental disorder characterized by speech and motor impairment

Abstract: Autophagy regulates the degradation of damaged organelles and protein aggregates, and is critical for neuronal development, homeostasis, and maintenance, yet few neurodevelopmental disorders have been associated with pathogenic variants in genes encoding autophagy-related proteins. We report three individuals from two unrelated families with a neurodevelopmental disorder characterized by speech and motor impairment, and similar facial characteristics. Rare, conserved, bi-allelic variants were identified in ATG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The ATG4D variations result in disruption of neuronal homeostasis, particularly in the axons and Purkinje cells, structures known to be dependent on basal autophagy. 38 , 39 , 40 , 41 An ATG4D :p.Ala430Thr variant previously has been associated with a recessive vacuolar storage disease in the Lagotto Romagnolo. 40 Although in these 3 Eurasier dogs clinical signs also support abnormal function of the cerebellum, some clear disparities exist both clinically and in MRI studies between the Lagotto Romagnolo and our dogs with a variant in the ATG4D gene.…”
Section: Discussionmentioning
confidence: 99%
“…The ATG4D variations result in disruption of neuronal homeostasis, particularly in the axons and Purkinje cells, structures known to be dependent on basal autophagy. 38 , 39 , 40 , 41 An ATG4D :p.Ala430Thr variant previously has been associated with a recessive vacuolar storage disease in the Lagotto Romagnolo. 40 Although in these 3 Eurasier dogs clinical signs also support abnormal function of the cerebellum, some clear disparities exist both clinically and in MRI studies between the Lagotto Romagnolo and our dogs with a variant in the ATG4D gene.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that dysfunctional autophagy leads to neurological dysfunction and neurodegenerative pathologies [ 32 34 ]. Aberrant expression of Atg4B and Atg5 has also been found in diabetic corneal nerves, suggesting that dysregulated autophagy is also involved in diabetic corneal neuropathy [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATG4D is the main delipidating enzyme of mATG8 and facilitates autophagosome formation, removing abnormal protein accumulation to protect neurons [ 40 42 ]. Deficiency or mutation of ATG4D causes cerebellar neurodegeneration and neurodevelopmental disorders [ 34 , 41 ]. However, there are no studies on ATG4D in diabetic corneal neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The number of human genomics studies who complete their first in vivo validations in Drosophila is growing. Additionally, a network of laboratories has united to use model organisms as rare disease profiling platforms, with Drosophila as one of the leaders in this movement ( Gahl et al, 2015 ; Huang et al, 2022 ; Morimoto et al, 2023 ; Srivastava et al, 2023 ). For more established models of diseases such as ALS, flies will continue to provide a platform for unbiased, in vivo screening for enhancers and suppressors of nerve degeneration and cell loss.…”
Section: Discussionmentioning
confidence: 99%